A Rapid Enrichment Technique for the Ultratrace Determination of Nickel in Water Samples Using a Nanofiber-composite Membrane Filter - MIZUGUCHI, Hitoshi; ISHIDA, Ryota; KOUNO, Yasushi; TACHIBANA, Tadahiko; HONDA, Tomomi; KIJIMA, Tatsuro; YAMAMOTO, Yuhei; TAKAYANAGI, Toshio (Analytical Sciences, 2018)
A new method for the rapid enrichment and highly sensitive determination of nickel ion has been developed by using a nanofiber-composite membrane filter, which was fabricated by stacking a nanofibrous material made of nylon 6 over a water-permeable membrane filter. The noncharged nickel-α-furil dioxime complex was adsorbed on a nanofibrous layer of the membrane filter under significantly higher flow rates than those used for conventional solid-phase extraction techniques. Highly sensitive determinations with detection limits at sub-parts per billion levels were achieved by enrichment from 50 mL of the complex solution, and the enrichment was completed within 3 min. The color that was developed on the membrane filter was successfully subjected to visual colorimetric analysis and quantitative determination by solid-phase spectrophotometry. In addition, colorimetric determination was feasible with a handheld spectrometer after elution of the colored agent with 50 μL of acetone. This combination of rapid enrichment and spectrometric measurement in a small-volume sample provides a useful analytical method suitable for on-site analysis, which requires neither expensive instruments nor high laboratory skills.